Pharmacokinetics and pharmacodynamics of new acute treatments for migraine. (4th March 2019) - Lupi, Chiara; Benemei, Silvia; Guerzoni, Simona; Pellesi, Lanfranco; Negro, Andrea
ABSTRACT: Introduction : Recommended medications for the acute treatment of migraine encompass triptans, nonsteroidal anti-inflammatory drugs (NSAIDs), and analgesics. While it is true that triptans have been the first successful mechanism-driven treatment in the field, recently, new targets involved in migraine pathogenesis have emerged and new drug classes have been studied for migraine attack therapy. Areas covered : Pharmacodynamics and pharmacokinetics of the new acute treatments of migraine (i.e. ditans, gepants, and glutamate receptor antagonists), considering also marketed drugs in new formulations and administration routes. Expert opinion : Research on the administration routes of marketed drugs was performed in order to improve, in accordance with basic pharmacokinetics parameters, the speed of action of these medications. Similar to the triptans, the new acute treatments are migraine-specific medications, acting on the trigeminovascular system, albeit with different mechanisms. Although available data do not conclusively indicate the superiority of a class over the others, the pharmacodynamics explains the peculiar tolerability and safety profile of different drug classes emerging from clinical trials. Further studies are needed to investigate the possibility of combining different drug classes to optimize the clinical response and the potential role of the novel drugs in medication-overuse headache.